PHENOL DESORPTION FROM ADSORBENT - A REVIEW (International Journal of Engineering Sciences & Management Research, 2015)
Recovery of used adsorbent is very important from the adoptability and economy point of view. Phenol is one of the major pollutants removed from wastewater by using adsorption technique. The problem in this process is regeneration of used adsorbent . The reuse of adsorbent is very important aspect of the adsorption process. Various thermal, chemical and other advanced techniques are available for the regeneration of adsorbent in phenol treatment. The current review aims at summarizing research carried out for desorption of phenol from adsorbent